Encountering steroid treatment induced tinea incognito: a case report - Reddy, Pallavi Gaddam; Maqsood, Maryam (International Journal of Research in Dermatology, 2023)
Tinea incognito refers to a type of dermatophyte infection that affects the skin, and its signs and symptoms upon presentation tend to appear permutated due to the prior use of immunosuppressants, corticosteroids or calcineurin inhibitors. We present a 42-year-old Asian (Indian) male patient with scaly erythematous rashes, mimicking annular erythema, and developing post-corticosteroid usage after an elective hair transplant procedure. The results of the biopsy reported that erythema annulare centrifugum (EAC) was absent, and the sample was suggestive of potential infective folliculitis. By day 3 of the presentation, with fungal stain tested positive for the presence of fungal infection. Based on this, the final diagnosis of tinea incognito was made. The final treatment prescribed for tinea incognito was an anti-fungal tablet of Itraconazole at a dose of 100 mg twice a day for 4 weeks, topical luliconazole, ciclopirox and anti-histamines for itching. Topical corticosteroids can change the clinical appearance of tinea by reducing erythema and scaling while enabling the fungus to grow freely without presenting the typical clinical indications of tinea. Practitioners should follow patients on corticosteroid treatment to alert them to potential cutaneous problems due to possible fungal infections, whenever warranted.